MINOR HEART ANOMALIES - E. V. Zemtsovskyi; E. G. Malev; M. Yu. Lobanov; N. N. Parfenova; S. V. Reeva; S. I. Khasanova; E. L. Belyaeva (Российский кардиологический журнал)
The paper attempts to revise the working classification of minor heart anomalies (MHA). It is proposed to exclude some syndromes and abnormalities which clearly have an independent clinical significance. The need for exclusion of prevalent normal variants, as well as anatomical and physiological characteristics of child’s heart, is justified. The inverse dynamics of selected MHA in older vs. younger age groups is demonstrated. The authors suggest that the current working classification should be modified.